Challenges in the Development and Use of Educational Materials in Schools - Dhungana, Babu Ram (Education Review Journal, 2025)
This article critically examines the development and use of teaching and learning materials (TLMs) in Nepalese schools, highlighting their pivotal role in enhancing educational outcomes. Drawing on both national performance data and international research, the study identifies the lack of effective instructional material usage as a major contributor to poor student achievement in Nepal. The paper underscores the significance of diverse, contextually relevant, and low-cost materials including locally sourced and ICT-integrated tools in promoting student engagement, conceptual understanding, and retention. Despite supportive policies and government budget allocations, the integration of TLMs remains inconsistent due to challenges such as traditional teacher-centered practices, inadequate training, limited innovation, and insufficient institutional support. The article offers evidence-based insights into the effectiveness of TLMs and provides actionable recommendations for teachers, parents, school management, and government bodies to improve the development, accessibility, and classroom application of TLMS. Strengthening the use of TLMs is essential for transitioning to inclusive, learner centered education and improving academic performance across Nepal’s diverse learning contexts.